Urban Development in Phnom Penh - World Bank Group (World Bank, Phnom Penh, 2017)
Urbanization presents an enormous opportunity for Cambodia. As has been demonstrated in countries around the world, urbanization is a driving force for growth and poverty reduction. Given Cambodia’s relatively early stage of urbanization, there is still an important opportunity to shape the future direction of urbanization. To positively shape the future of Cambodian cities, strong institutions for urban planning and management, collaboration across agencies, and a sustained commitment to the importance of principles of sustainability and inclusion will be needed. This report provides a summary of key issues related to urbanization in Cambodia, with a particular focus on Phnom Penh given its role as the country’s largest and most prosperous city. Section one provides context on urbanization, institutional and financial arrangements, urban planning, urban service delivery, and sustainability and inequality. Section two focuses in on three underlying constraints to efficient urbanization and section three includes priorities for Phnom Penh as a competitive, sustainable, and inclusive city.